Diet composition of carnivorous fishes in Dulag, Leyte - Aldiano, Thea L.; dela Cruz, Margarita (2012)
The aim of this research is to determine the stomach content of carnivorous fishes in the marine waters of Dulag, Leyte. Three species of carnivorous fishes (Auxis rochei, Atule mate, and Lutjanus malabaricus) were sampled twice a month from November 2011 to February 2012. A total of 162 stomachs were acquired and dissected, of which 76 (48.72%) contained completely digested items. Sex and stages of maturity were also recorded. Prey items were categorized and classified. The results showed that the most important food item of carnivorous fishes by frequency of occurrence are crustaceans-- penaeid shrimps, crabs (42.66%) followed by small/juvenile fishes (30.14%) indicating that crustaceans and fishes directly play an important role in the ecosystem of the open ocean for carnivorous fishes. A number of stomach samples contained partially digested food items, in which sample visual identification was not possible. Moreover, results depicted mature fishes having the most significant amount of prey items in the stomach. With the diversity of prey items found, an indication that prey communities in the open waters are rich is logical, though further studies should be done regarding the topic.
Research paper (Bachelor of Science in Biology)--University of the Philippines, Tacloban.
Keywords: Carnivorous fishes -- Philippines -- Dulag, Leyte; Science and Technology